Learning Obstacles in Fraction Addition: An Analysis of Ontogenic, Epistemological, and Didactical Factors Among Elementary Students - Kadek Herawati; Herlina Herlina; Sisriawan Lapasere; Zulnuraini Zulnuraini; Ammar Abdullah Joni Guci; Surahman Wilade (Journal of Innovation and Research in Primary Education, 2026)
Understanding fraction addition is an essential foundational competence in elementary mathematics learning, yet many students experience persistent difficulties. These difficulties can be understood as learning obstacles that hinder students' learning processes and outcomes. This study aimed to analyze learning obstacles experienced by grade VB students at SD Negeri 15 Palu regarding fraction addition concepts. The research employed a descriptive qualitative approach with a case study design. Participants consisted of one mathematics teacher and three purposively selected students based on low-level fraction addition understanding. Data collection techniques included classroom observations, structured interviews, conceptual understanding tests, and documentation. Data analysis was conducted interactively through data collection, condensation, presentation, and conclusion drawing stages. Results indicated that students experienced three types of learning obstacles: ontogenic, epistemological, and didactical. Ontogenic obstacles were evident in students' low learning readiness, encompassing physical, mental, emotional, and prior knowledge dimensions (47.72% and 45.45% readiness levels). Epistemological obstacles were manifested in limited conceptual understanding, errors in denominator equalization, numerator determination, and procedural application. Didactical obstacles were not significantly found, as the teacher demonstrated highly effective teaching skills (84.32% performance level). These findings indicate that students' learning difficulties in fraction addition are predominantly caused by student readiness and conceptual understanding factors rather than instructional quality. This study provides important implications for developing mathematics learning that strengthens learning readiness and meaningful conceptual understanding in elementary schools.